Measured versus label declared macronutrient and calorie content in Colombian commercially available whey proteins - Andrés Zapata-Muriel; Patricia Echeverry; Trisha A. Van Dusseldorp; Jennifer Kurtz; Matías Monsalves-Alvarez (Taylor & Francis Group, 2022)
Whey protein (WP) supplements have grown in popularity for exercising populations to enhance muscle protein synthesis and promote recovery. The purpose of this investigation was to examine the macronutrient profile, especially protein, of commonly sold protein powder brands in the Colombian (South America) sports supplement market. Eleven popular whey proteins supplements made and sold on the Colombian market were sampled and determined the humidity, ash, total carbohydrates, fat, proteins, and calories (kcal). The mean calorie content declared by product labeling was significantly lower (p < 0.05) than measured (labeled 349.8 ± 20.3 kcal; analyzed 368.2 ± 14.9 kcal). Carbohydrate content was higher than labeled on average (labeled 3.5 ± 6 g/100 g; analyzed 21.9 ± 12.5 g/100 g) (p < 0.05). The protein content on the labels showed a significantly higher content, on average, than analyzed in all samples (labeled 81.4 ± 7.4; analyzed 65.7 ± 14.1) (p < 0.05). These data suggest, that for brands analyzed in this research, nutrient labels may be misleading, especially regarding protein, carbohydrate, and total calorie content. Consumers should diligently read, but also learn the different product labeling; however, brands should emphasize on testing their products and add amino acid profiles to guarantee quality of their products.